2018
DOI: 10.1186/s40580-018-0170-1
|View full text |Cite
|
Sign up to set email alerts
|

Peptide–nanoparticle conjugates: a next generation of diagnostic and therapeutic platforms?

Abstract: Peptide–nanoparticle conjugates (PNCs) have recently emerged as a versatile tool for biomedical applications. Synergism between the two promising classes of materials allows enhanced control over their biological behaviors, overcoming intrinsic limitations of the individual materials. Over the past decades, a myriad of PNCs has been developed for various applications, such as drug delivery, inhibition of pathogenic biomolecular interactions, molecular imaging, and liquid biopsy. This paper provides a comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
121
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(122 citation statements)
references
References 131 publications
(146 reference statements)
0
121
0
1
Order By: Relevance
“…Peptides different from antibodies do not destroy specificity or affinity and are small enough to weaken the vascular barrier to the lesion sites conveniently. The combination of peptides and nanoparticles overcomes the delivery barriers of many traditional drugs and provides a powerful strategy for the study of nanomedicines [26]. The previous study had demonstrated that the peptide VHPKQHR has high affinity with injured endothelial cells that are characteristic of atherosclerosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Peptides different from antibodies do not destroy specificity or affinity and are small enough to weaken the vascular barrier to the lesion sites conveniently. The combination of peptides and nanoparticles overcomes the delivery barriers of many traditional drugs and provides a powerful strategy for the study of nanomedicines [26]. The previous study had demonstrated that the peptide VHPKQHR has high affinity with injured endothelial cells that are characteristic of atherosclerosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…They are classified according to their architecture into nanospheres, nanocapsules, conjugated polymers, and polyelectrolyte complexes [ 31 ]. Nanoparticles can be used to transport proteins and peptides, whose conjugation generates a synergistic effect that improves the limitations of each one of the materials and achieves uses, such as inhibition of the interactions of pathogenic proteins and high sensitivity in molecular imaging [ 32 , 33 , 34 ].…”
Section: Efforts To Overcome Peptide Limitationsmentioning
confidence: 99%
“…Several attempts have already been made to measure the transcytosis or penetration of diverse therapeutic agents through the BBB. In particular, surface-functionalized nanoparticles accompanied by encapsulation or surface-modification of drugs are an emerging technology for penetrating the BBB [103][104][105]. Chai et al developed red blood cell membrane-coated nanoparticles with a CDX peptide, which is derived from candoxin and shows a high-binding affinity with nicotinic acetylcholine receptors on the surface of the endothelial cell [106].…”
Section: Future Perspective and Conclusionmentioning
confidence: 99%